2020
DOI: 10.1002/jccs.201900526
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanism and kinetic modeling of CO hydrogenation reaction over the impregnated Co‐Ni/Al2O3 catalyst

Abstract: An investigation of the kinetic and mechanism of CO hydrogenation reaction was performed on impregnated Co‐Ni/Al2O3. Determination of kinetic parameters from the experiments was carried out in a micro fixed‐bed reactor. Kinetic evaluations were performed under various operational conditions of T = 473–673 K, p = 1–14 bar, H2/CO = 1–3, and GHSV = 4,500 hr−1. Kinetic models and rate equations for CO consumption were obtained by using two main‐type rate equations of Langmuir‐Hinshelwood‐Hougen‐Watson (LHHW) and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although linear equations are the common description forms for most of the reaction kinetics, researchers have found that in some cases linear forms could not describe the process well 43 . Non‐linear description has received growing attention in recent research and the method is indeed better for parameter calculations as the non‐linear form is consistent with the raw kinetic equations 44,45 . In the present study, the non‐linear method was utilized, and Origin version 9.4 was used to determine the kinetic parameters.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although linear equations are the common description forms for most of the reaction kinetics, researchers have found that in some cases linear forms could not describe the process well 43 . Non‐linear description has received growing attention in recent research and the method is indeed better for parameter calculations as the non‐linear form is consistent with the raw kinetic equations 44,45 . In the present study, the non‐linear method was utilized, and Origin version 9.4 was used to determine the kinetic parameters.…”
Section: Resultsmentioning
confidence: 97%
“…43 Non-linear description has received growing attention in recent research and the method is indeed better for parameter calculations as the non-linear form is consistent with the raw kinetic equations. 44,45 In the present study, the non-linear method was utilized, and Origin version 9.4 was used to determine the kinetic parameters. For the non-linear fitting, the rate equations with an indefinite integral form are listed in Table 7.…”
Section: Ta B L E 7 Non-linear Form Of Rate Equationmentioning
confidence: 99%
“…Some investigators have reported the effect of operation parameters on the product distribution from cobalt-based catalysts [19][20][21][22][23] and showed that the olefin contents of the product spectrum decreased with increasing pressure, which was consistent with previous investigations. [24][25][26] In our previous works we used Co-Ni catalyst for production of lower olefins; 27,28 in these works, the preparation conditions of co-precipitated sample were optimized 27 and the kinetics and activity of impregnated sample were investigated. 28 In the current work we investigated the influences of process variables on the catalytic behavior of Co-Ni/Al 2 O 3 -impregnated nanocatalyst for lower olefin production.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In our previous works we used Co-Ni catalyst for production of lower olefins; 27,28 in these works, the preparation conditions of co-precipitated sample were optimized 27 and the kinetics and activity of impregnated sample were investigated. 28 In the current work we investigated the influences of process variables on the catalytic behavior of Co-Ni/Al 2 O 3 -impregnated nanocatalyst for lower olefin production. In our previous works we investigated the impact of reaction conditions on the catalytic performance of different prepared catalytic systems.…”
Section: Introductionmentioning
confidence: 99%